Mass Accretion, Spectral, and Photometric Properties of T Tauri Stars in Taurus Based on TESS and LAMOST - Chia-Lung Lin; Wing-Huen Ip; Yao Hsiao; Tzu-Heng Chang; Yi-han Song; A-Li Luo (The Astronomical Journal, 2023)
We present the analysis of 16 classical T Tauri stars (CTTSs) using LAMOST and TESS data, investigating spectral properties, photometric variations, and mass accretion rates. All 16 stars exhibit emissions in H α lines, from which the average mass accretion rate of 1.76 × 10 ^−9 M _⊙ yr ^−1 is derived. Two of the stars, DL Tau and Haro 6-13, show mass accretion bursts simultaneously in TESS, ASAS-SN, and/or the ZTF survey. Based on these observations, we find that the mass accretion rates of DL Tau and Haro 6-13 reach their maxima of 2.5 × 10 ^−8 M _⊙ yr ^−1 and 2 × 10 ^−10 M _⊙ yr ^−1 , respectively, during the TESS observation. We detect 13 flares among these stars. The flare frequency distribution shows that the CTTSs’ flare activity is not only dominated by strong flares with high energy but also much more active than those of solar-type and young low-mass stars. By comparing the variability classes reported in the literature, we find that the transition timescale between different classes of variability in CTTSs, such as from stochastic (S) to bursting (B) or from quasi-periodic symmetric to quasi-periodic dipping, may range from 1.6 to 4 yr. We observe no significant correlation between inclination and mass accretion rates derived from the emission indicators. This suggests that inner disk properties may be more important than those of outer disks. Finally, we find a relatively significant positive correlation between the asymmetric metric M and the cold disk inclination compared to the literature. A weak negative correlation between the periodicity metric Q value and inclination has also been found.